Knee Osteoarthritis Severity in Relation to Neutrophil- Lymphocyte Ratio (Indian Journal of Forensic Medicine & Toxicology, 2021)
Background: Osteoarthritis is a disease with a significant inflammatory component. Neutrophil-lymphocyteratio (NLR) level is a marker to determine inflammation. The study aimed to evaluate the association betweenseverity of knee osteoarthritis and NLR.Methods: A case-control study conducted inAl-Zahrawiduring June 2017 to June 2018. A total of 100 kneeosteoarthritis were recruited and 50 healthy subjects as a control group.Results: NLR was significantly higher in knee osteoarthritis than controls, the mean vale was (2.19±0.72)and (1.97±0.88), respectively. Older age, chronic pain, prolong onset of diagnosis and high NLRweresignificantly associated with severe osteoarthritis.Conclusions: Knee osteoarthritis had higher NLR compared to healthy people. Higher NLR is associatedwith severity of knee osteoarthritis and it is a poor indicator.